2022
DOI: 10.1097/nur.0000000000000643
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Nurse Specialist–Led Initiative to Reduce Catheter-Associated Urinary Tract Infection Rates Using a Best Practice Guideline

Abstract: The purpose of this clinical nurse specialist-led initiative was to reduce catheter-associated urinary tract infection rates to less than 1 infection per 1000 catheter days, to reduce catheter device utilization, and to improve staff adherence to documentation requirements on a traumatic brain injury rehabilitation unit. Description of the Project: Catheter-associated urinary tract infections are costly hospitalacquired infections increasing length of stay and morbidity for patients. Following an education int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
2
2
0
1
Order By: Relevance
“…The investigator's perspective is that most of the people in rural areas of Upper Egypt tend to marry in early adulthood, and other single patients could be in urban areas or aged less than 20 years. The present study finding was consistent with (Alhabdan et al, 2023) [15] , who revealed the majority of the participants were married. The present study finding contradicted (Hak et al, 2022) [14], who indicated that one-third of the study group were married.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The investigator's perspective is that most of the people in rural areas of Upper Egypt tend to marry in early adulthood, and other single patients could be in urban areas or aged less than 20 years. The present study finding was consistent with (Alhabdan et al, 2023) [15] , who revealed the majority of the participants were married. The present study finding contradicted (Hak et al, 2022) [14], who indicated that one-third of the study group were married.…”
Section: Discussionsupporting
confidence: 93%
“…The current study results are consistent with those of Sultan et al (2022) [22] , who indicated that head trauma was the most common reason for ICU admission for both groups, which means that head trauma is a risk factor for UTI occurrence. These results were supported by (Pajerski et al, 2022) [15] , who showed that patients with traumatic brain injury were at increased risk of developing a UTI.…”
Section: Discussionsupporting
confidence: 52%
“…A reduction of incidence of urinary tract infection is made possible by adopting a few measures such as application of a checklist and training packages for a proper urinary catheter insertion (hand hygiene with 2% chlorhexidine, connection of the collection bag to the catheter before its insertion) [ 75 ], teach a group of nurses to remove nonessential urinary catheters [ 76 , 77 ]. Since a period of urinary catheterization of more than 4 days significantly increases the risk of infection [ 74 ], if possible, it would be appropriate to remove the catheters before.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Penelitian ini mengkorelasikan adanya nyeri pasca operasi dan kelelahan dengan kurangnya informasi dan persiapan pra operasi yang tidak memadai. (Dahodwala et al, 2020;Pajerski et al, 2022). Pentingnya edukasi persiapan operasi menuntut perawat untuk mampu meningkatkan kompetensi sebagai edukator.…”
Section: Pembahasanunclassified